Study of the competition tactics of Chinese and world top swimmers in recent years - Li, Z.; Yang, G.; Chen, A.; Liu, J.; Zhen, Z.; Li, J. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
This abstract expounds on the tactical features and the differences of Chinese and World top swimmers based on the data of percentage of each split section collected in the recent Olympic Games and China National Games. Methods Observation, Statistics and Woks References Results In the recent four Olympic Games, the percentage of split section of the world famous swimmers in various 100-metre styles is shown below: the first split of freestyle calculated as 47.8% - 48.62%; backstroke, 47.32 - 48.94%, increased at first and decreased afterwards; 46.47% - 47.20% for butterfly. The percentage rate of the Chinese freestyle and backstroke swimmers at the first split section shows relatively high, indicating that they swim too slowly at the first split , and thus the pace is not as even as that of the world top swimmers. As far as 200-metre and 400-metre events are concerned, there shows no great difference between the world top swimmers and the Chinese swimmers whose tactics adopted is even pace swimming. For women's 800-metre freestyle, the percentage of the first split for the world top athletes is 12.13% - 12.20% and for the Chinese swimmers, however, is 12.03% - 12.01%, meaning that the Chinese athletes swim too fast at the first split. Judging from recent men's 1500m freestyle events, there have been no great changes in the percentage of each split section.(1) (2) (3). The athletes basically apply the tactics of even pace swimming, but with a stable increase of swimming speed, which proves that the training level of men's long distance freestyle is gradually increased. Discussion/Conclusions For 100-metre backstroke, the percentage difference for the world top swimmers shows an increase at the first split and a decrease at the later split; for 100-metre breaststroke and butterfly, the percentage of the first split and the later split is nearly the same; but for 100-metre freestyle, the percentage of the first split and later split for the world top swimmers tends to be increased; the competition tactics adopted by Chinese and foreign athletes is quite the same in the various 200-metre styles; for 400-metre freestyle, the tactics of even pace swimming is preferable to both Chinese and world top swimmers.